Exergy analysis and thermoeconomic cost accounting of a Combined Heat and Power steam cycle integrated with a Multi Effect Distillation-Thermal Vapour Compression desalination plant. (1st October 2017) - Catrini, P.; Cipollina, A.; Micale, G.; Piacentino, A.; Tamburini, A.
Highlights: A Combined Heat and Power plant coupled with Multiple Effect Distillation is examined. An innovative productive structure is proposed for thermoeconomic cost accounting. Exergetic and exergoeconomic costs are calculated for all the material streams. The concentrated brine is alternatively considered a residue to be disposed or a resource to be exploited. Reverse Electrodyalisis is adopted for exergy recovery from the concentrated brine. Abstract: In this paper an exergy analysis and thermoeconomic cost accounting of a Combined Heat and Power steam cycle integrated with Multi Effect Distillation-Thermal Vapour Compression plant is performed; the goal of the study is to show how these methodologies provide a rational criterion to allocate production costs on electricity and freshwater in such a dual purpose system. After a brief overview on the methodology and a description of reference plant, exergy analysis is carried out to calculate exergy flows and exergy efficiencies at component level. A detailed description of the adopted thermoeconomic model is given. In a first scenario, cost accounting is performed assuming that the concentrated brine is disposed back to sea, thus being its exergy content definitively wasted; furthermore, a sensitivity analysis is carried out in order to assess the changes in the unit cost of electricity and freshwater with several design and operation parameters. In a second scenario, conversely, part of brine exergy is used in a Reverse Electrodialysis unit to produce further electricity. In both cases results show that high unit costs are obtained for the material streams or energy flows which involve major exergy destruction along their production process, particularly freshwater in the former configuration and Reverse Electrodialysis electric output in the latter one.